Hay fever, eczema, and wheeze: a nationwide UK study (ISAAC, international study of asthma and allergies in childhood). Issue 3 (1st September 1999) - Austin, Jane B; Kaur, Balvinder; Anderson, H Ross; Burr, Michael; Harkins, Leigh S; Strachan, David P; Warner, John O
Abstract : OBJECTIVES: To describe the prevalence of atopic symptoms in children throughout the UK. METHOD: A questionnaire survey of 12–14 year olds throughout England, Wales, Scotland, and the Scottish Islands using the international study of asthma and allergies in childhood (ISAAC) protocol. RESULTS: A total of 27 507 (86%) children took part. Recent rhinoconjunctivitis was reported by 18.2%, with 6.2% reporting symptoms between March and September; 16.4% reported itchy flexural rash in the past 12 months. The prevalence of atopic symptoms was higher in girls and subjects born within the UK. The prevalence of severe wheeze was highest in subjects reporting perennial rhinoconjunctivitis, as opposed to summertime only symptoms. Winter rhinoconjunctivitis was associated with severe wheeze and severe flexural rash. One or more current symptoms were reported by 47.6% of all children and 4% reported all three symptoms. CONCLUSION: In general, geographical variations were small but the prevalence of symptoms was significantly higher in Scotland and northern England. The study demonstrates the importance of atopic diseases both in their own right and in association with asthma.